Autophagy deficiency protects against ocular hypertension and glaucoma - Angela Dixon; Myoung Sup Shim; April Nettesheim; Aislyn Coyne; Chien-Chia Su; Haiyan Gong; Paloma B. Liton (Autophagy Reports)
Glaucoma encompasses a spectrum of disorders characterized by the chronic degeneration of retinal ganglion cell (RGC) axons and the progressive loss of RGCs, resulting in visual impairment. In this study, we investigated the effect of autophagy deficiency on two glaucoma hypertensive models, the DBA/2J spontaneous glaucoma model, and the TGFβ2 (transforming growth factor β2) chronic ocular hypertensive model. For this, we used the Atg4b−/− and DBA/2J-Atg4b−/− mice, this latter generated in our laboratory via CRISPR/Cas9 technology, which display impaired autophagy. In contrast to littermate WT controls, mice deficient in Atg4B, did not develop glaucomatous elevation of intraocular pressure (IOP). Moreover, autophagy deficiency protected against RGC death and optic nerve atrophy. Collectively, our data supports a pathogenic role of autophagy in the context of ocular hypertension and glaucoma.Abbreviations: ATG4B: Autophagy-related 4B; BAX: BCL2-associated X protein; BECN1: Beclin 1; BID: BH3 interacting domain death agonist; CASP8: Caspase 8; IOP: Intraocular Pressure; MAP1LC3B: microtubule-associated proteins 1B; ON: Optic Nerve; RGC: Retinal Ganglion Cells; SQSTSM1: Sequestosome 1; TBK1: TANK-binding kinase 1; TGFβ2: Transforming Growth Factor β2; WT: Wild Type.